1983
DOI: 10.1071/wr9830303
|View full text |Cite
|
Sign up to set email alerts
|

The Ingestion of Artifically Coloured Grain by Birds, and its Relevance to Verebrate Pest Control

Abstract: In 23 field and aviary trials with several species of ground-feeding birds, the short-term uptake of grain coloured red, blue, green, yellow and black was compared with that of natural (uncoloured) grain. In all trials, one or more of the artificial colours caused a significant depression in the amount of food eaten. Although the preferences for grain of the five colours varied from trial to trial, the uptake of both blue and green grain was significantly lower than for untreated grain in all trials, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Granivorous birds may also forage according to the contrast of food item and background and not simply according to the colour of the food. This may explain the inconsistent results in food choice experiments with wild birds offered differently coloured food items 15–17…”
Section: Discussionsupporting
confidence: 79%
“…Granivorous birds may also forage according to the contrast of food item and background and not simply according to the colour of the food. This may explain the inconsistent results in food choice experiments with wild birds offered differently coloured food items 15–17…”
Section: Discussionsupporting
confidence: 79%
“…fruit vs insect; Gamberale-Stille et al 2007). While natural or green-dyed fruits or test baits appear generally to be less preferred than those of other colours (Brunner & Coman 1983;Rathore 1985;Mastrota & Mench 1994;Moran 1999;Weser & Ross 2013), the variation noted in responses suggests, as Kalmbach and Welch (1946) did in general terms, that there are potential differences between bird species in response to colours. Therefore, before any change of bait colour is proposed, more research is needed on the responses of the most at-risk New Zealand native birds to differently-coloured baits, as few species and limited colours have been tested to date.…”
Section: Background Informationmentioning
confidence: 97%
“…Naturally occurring blue fruits, while more common than green ones, are much less common than red/orange or purple/black fruits (Lord & Marshall 2001), and generally less preferred than red or black in choice tests (e.g. Brunner & Coman 1983;Larrinaga 2011;Duan & Quan 2013). In assessing risks prior to a proposed aerial poisoning operation, Oppel et al (2016) found that Henderson crakes (Zapornia atra) ate no dry pellets but less moistened blue-dyed cereal pellet bait than green-dyed bait.…”
Section: Green Dye To Minimise New Zealand Bird Interactions With Toxmentioning
confidence: 99%
“…Unfortunately, Received 28 November 1996;accepted 7 April 1997 individuals from a wide range of bird species have been killed in such operations (Spurr 1993(Spurr , 1994. Measures employed to reduce the risk of such nontarget mortality include: improvements in pelleting procedures to reduce fragmentation of aerially sown baits (Morgan 1994); banning of raspberry lure implicated in bird deaths in the mid 1970s (Harrison 1978); addition of green dye to baits to make them less attractive to birds (Caithness & Williams 1971;Brunner & Coman 1983); and addition of cinnamon oil as a bird repellent (Udy & Pracy 1981;Pracy et al 1982).…”
Section: Introductionmentioning
confidence: 99%